British Silurian Myodocope Ostracods. Issue 651 (15th March 2019) - Perrier, Vincent; Siveter, David J.; Williams, Mark; Palmer, Douglas
Abstract: The Silurian myodocope ostracods from Britain comprise six families, 12 genera and 22 species, plus three species in open nomenclature. New material includes representatives of the families Bolbozoidae, Entomozoidae, Cypridinidae and Seminovidae n. fam.; newly described genera and species are Seminova gen. nov., Oculparva moncola gen. et sp. nov., Piscarista sagenata gen. et sp. nov., Nudator inflatus gen. et sp. nov., Nudator angiportatus gen. et sp. nov., Nudator artumatus gen. et sp. nov. and Bolbozoe psittaca sp. nov. Fine biostratigraphic control allows the development of a myodocopid biozonation for the Wenlock and Ludlow series. Seven myodocopid biozones are established, from the early Homerian (Wenlock) to the late Ludfordian (Ludlow) stages. This biozonation allows inter-continental correlation of Silurian successions in Europe, Arctic Russia and Central Asia. Les ostracodes Myodocopes du Silurien britannique RÉSUMÉ La faune d'ostracodes myodocopes du Silurien de Grande-Bretagne, comprend six familles, 12 genres et 22 espèces, plus trois espèces en nomenclature ouverte. Le nouveau matériel comprend des représentants des familles Bolbozoidae, Entomozoidae, Cypridinidae et Seminovidae n. fam.; et sont décrit les nouveaux genres et espèces: Seminova gen. nov., Oculparva moncola gen. et sp. nov., Piscarista sagenata gen. et sp. nov., Nudator inflatus gen. et sp. nov., Nudator angiportatus gen. et sp. nov., Nudator artumatus gen. et sp. nov. et Bolbozoe psittaca sp. nov. Le fin contrôle biostratigraphique permet le développement d'une biozonation des ostracodes myodocopes pour le Wenlock et le Ludlow. Sept biozones à myodocopes peuvent être identifiés, du début de l'Homérien à la fin du Ludfordien. Cette biozonation permet une corrélation inter-continentale entre les successions siluriennes d'Europe, de Russie arctique et d'Asie centrale. Ostracoden der Ordnung Myodocopa aus dem Silur Großbritanniens ZUSAMMENFASSUNG Die silurischen myodocopen Ostrakoden aus Großbritannien umfassen sechs Familien, 12 Gattungen und 22 Arten, sowie drei Arten in offener Nomenklatur. Zu dem neuen Material gehören Vertreter der Familien Bolbozoidae, Entomozoidae, Cypridinidae und Seminovidae n. fam.; die folgende Gettungen und Arten werden beschrieben: Seminova gen. nov., Oculparva moncola gen. et sp. nov., Piscarista sagenata gen. et sp. nov., Nudator inflatus gen. et sp. nov., Nudator angiportatus gen. et sp. nov., Nudator artumatus gen. et sp. nov. und Bolbozoe psittaca sp. nov. Feinste biostratigraphische Auflösung ermöglicht die Entwicklung einer Biozonierung der myodocopen Ostrakoden für das Wenlock und das Ludlow. Sieben Biozonen können vom frühen Homerium (Wenlock) bis zum späten Ludfordium (Ludlow) bestimmt werden. Diese Biozonierung ermöglicht eine interkontinentale Korrelation silurischer Abfolgen innerhalb Europas, im arktischen Russland und in Zentralasien. Великобританские силурийские миoдокопидные oстркоды РЕЗЮМЕ Силурийская фауна миодокопидных остракод Великобританий состоит из 22 видов, которые относятся к 12 родам, шести семействам, к ним добавляются 3 вида открытой номенклатуры. Новы материал относится к семействам Bolbozoidae, Entomozoidae, Cypridinidae, а также к Seminovidae n. fam. и Seminova gen. nov., Oculparva moncola gen. et sp. nov., Piscarista sagenata gen. et sp. nov., Nudator inflatus gen. et sp. nov., Nudator angiportatus gen. et sp. nov., Nudator artumatus gen. et sp. nov. и Bolbozoe psittaca sp. nov. Хороший биостратиграфический контроль способствовал разработку миодокоповой биозонаций для венлоксого и лудловского отделов силура. Семь биозонов устновлено для временного интервала от хомера (венлок) до позднего лудфорда (лудлов). Зональная шкала миодокопид пригодна для корреляций силурийских отложений в пределах Европы, арктической части России и Центральной Азии.